New perspectives in bean breeding in Arusha as part of the SADC/CIAT Regional Bean Program - Youngquist, W (International Center for Tropical Agriculture, 1992)
The needs in bean breeding are undergoing constant evolution as new varieties come on the market and the needs of our farmers change. However, there are many problems which seem always to be with us and old solutions and methodologies still represent the best tactics. There are two main areas that the bean breeder in Arusha will be addressing. These are germplasm supply and scientific development. Germplasm can come from anywhere in the world and CIAT will try and facilitate its movement. National program scientists should have good access to all germplasm. The second area covers how the germplasm is evaluated. Proper trial designs need to be used, correct analysis of the data is imperative, proper assessment of the conclusions need to be made and a plan developed to implement the conclusions